If distinct integers $a,b,c,d$ are consecutive terms of an arithmetic progression such that $$a^2 + b^2 + c^2=d$$ then $a+b+c+d$ equals? $$(A)\ 0 \quad (B)\ 1 \quad (C)\ 2 \quad (D)\ 4$$ Here is what I tried: assume the common difference is $x$. Thus, $$a^2 + a^2 + 2ax + x^2 +a^2 +4ax +4x^2=a + 3x$$ That is, $$3a^2 + 6ax + 2x^2=a + 3x$$ First I assumed it as a quadratic in $a$ and solved for it. $$a=\frac{(1-6x) \pm \sqrt{12x^2-48x +1}}{6}$$ but to no avail. Then I assumed it as a quadratic in $x$ and got: $$x=\frac{(3-6a) \pm \sqrt{12a^2 -36a +81}}{6}$$ And I noticed that I'm stuck. Please help. Thanks in advance!

Edit: I made a calculation error as pointed out by multiple answers, and so the equation should have been $$3a^2 + 6ax + 5x^2=a + 3x$$ which leads to different solutions.

  • 1
    $\begingroup$ If I'm not mistaken, you can't assume that they are one after another in the arithmetic progression, right? You might need to make the terms a bit different. I'm not sure if it's helpful, but it might be better to write the sum as $a^2 + a + b^2 + b + c^2 +c$. $\endgroup$ Jun 30, 2019 at 10:08
  • $\begingroup$ @CameronWilliams with reference to other problems in the same book, it should mean that they are consecutive terms. $\endgroup$ Jun 30, 2019 at 10:10
  • 1
    $\begingroup$ In that case, I edited your post to make this clear for others! I hope you don't mind! $\endgroup$ Jun 30, 2019 at 10:21

4 Answers 4



Let $a,b,c,d$ be $A-3D, A-D, A+D, A+3D$



The discriminant $$(6D+1)^2-12(11D^2-3D)=-96D^2+48D+1=1+6-96\left(D-\dfrac14\right)^2\le7$$ has to be perfect square

  • $\begingroup$ I'm sorry, I could not proceed. Could you please explain the cryptic last line "has too perfect square"? $\endgroup$ Jun 30, 2019 at 10:21
  • 2
    $\begingroup$ @AryanSonwatikar, Has to be perfect square. $\endgroup$ Jun 30, 2019 at 10:22
  • $\begingroup$ Oh, okay. So I simply need to check for discriminant equals $0,1,4$ right? $\endgroup$ Jun 30, 2019 at 10:24
  • $\begingroup$ Okay, $D=0.5=A$ which leads me to the answer as option $C$ which matches with the answer key. Thank you so much! $\endgroup$ Jun 30, 2019 at 10:32
  • 1
    $\begingroup$ @AryanSonwatikar, Welcome! Had it been odd number of terms, we would have chosen $$\cdots,A-D,A, A+D,\cdots$$ $\endgroup$ Jun 30, 2019 at 10:38

Your correct equation is $$3a^2+a(6x-1)+5x^2-3x=0$$ whose discriminant is $$(6x-1)^2-12(5x^2-3x)=1+6-24\left(x-\dfrac12\right)^2\le7$$

or the equation can be formed as $$5x^2+x(6a-3)+3a^2-a=0$$

Calculate the discriminant which needs to be perfect square


You made a slight error, this needs to be $5x^2$ and not $2x^2$.

So you have this equation $$3a^2+a(6x-1)+(5x^2-3x)=0$$

This equation has discriminant $\Delta=-24x^2+24x+1$

The way to solve this for Diophantine equations is to introduce an integer $m$ such that $\Delta=m^2$ (because we need the square root to be an integer for the solution $a$ to have a chance to be an integer).

Now we are left to solve $$24x^2-24x+(m^2-1)=0$$

Once again since $x$ is an integer, the discriminant $\delta=672-96m^2=96(7-m^2)$ should also be a perfect square.

In this case notice that $m$ can only take values $\ 0,1,2\ $ since we need $\delta\ge 0$

$96=2^5\times 3$ so we need to multiply by $6$ to have perfect square and the solution is $m=1$.

Finally $x=\dfrac{24\pm\sqrt{96\times 6}}{2\times 24}\in\{0,1\}$

The last step is to verify the $x$ found satisfy the original problem.

  • $x=0$

Then $a=b=c=d\implies d=3a^2=a\implies a=\frac 13$ which is not an integer. So this is not a valid solution.

  • $x=1$

With this value we arrive to $$3a^2+5a+2=(a+1)(3a+2)=0$$

And only $a=-1$ is a valid integer.

Conclusion: $a=-1,\ b=0,\ c=1,\ d=2$

We can verify $a^2+b^2+c^2=1+0+1=2=d$ and $a+b+c+d=-1+0+1+2=2$.


Let $x$ be the common difference.

From $a^2+b^2+c^2=d$, we get $d > 0$,

Since $a,b,c,d$ are distinct, we get $x\ne 0$.

If $x < 0$, then $c > d$, hence $$c^2 > d^2\ge d=a^2+b^2+c^2 > c^2$$ contradiction.

Hence $x > 0$.

\begin{align*} \text{Then}\;\;&a^2+b^2+c^2=d\\[4pt] \implies\;&(b-x)^2+b^2+(b+x)^2=b+2x\\[4pt] \implies\;&3b^2+2x^2=b+2x\\[4pt] \implies\;&b(1-3b)=2x(x-1)\\[4pt] \implies\;&b(1-3b)\ge 0\\[4pt] \implies\;&b=0\;\;\\[4pt] \implies\;&2x(x-1)=0\\[4pt] \implies\;&x=1\\[4pt] \implies\;&a,b,c,d=-1,0,1,2\\[4pt] \implies\;&a+b+c+d=2\\[4pt] \end{align*}


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.